Identifying monetary policy in a small open economy under flexible exchange rates - David O. Cushman; Tao Zha (Federal Reserve Bank of Atlanta, 1995)
Previous empirical study on the effects of monetary policy shocks in small open economies has produced exchange rate responses that are inconsistent with existing open economy macroeconomic theory. We argue that a careful identification of monetary policy in an explicit open economy setting is required. Using Canada as a case study, we specify and estimate a vector-autoregressive model that focuses on the identification of contemporaneous monetary policy, and we obtain tightly estimated results overall. The resulting dynamic responses to the identified monetary policy shock as well as to a foreign shock are consistent with traditional open economy analyses and highlight the importance of the exchange rate as a transmission mechanism.
Keywords: 330; Foreign exchange rates; Monetary policy